Great Northern Railway : a history - Hidy, Ralph W. (Ralph Willard), 1905-1977 (Fesler-Lampert Minnesota heritage book series., 2004)
The Great Northern Railway highlights the changes brought on by economic, political, social, and technological advances, including world wars and tighter government restrictions. Illustrated with more than two hundred maps, period photographs, and drawings, the volume also includes appendixes listing the original track-laying history, track removals, ruling grades on main freight routes, and main line ruling grades from Minneapolis to Seattle.